2015
DOI: 10.1242/jcs.177675
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin and LIF/Stat3 signaling pathways converge on Sp5 to promote mouse embryonic stem cell self-renewal

Abstract: Activation of leukemia inhibitor factor (LIF)–Stat3 or Wnt/β-catenin signaling promotes mouse embryonic stem cell (mESC) self-renewal. A myriad of downstream targets have been identified in the individual signal pathways, but their common targets remain largely elusive. In this study, we found that the LIF–Stat3 and Wnt/β-catenin signaling pathways converge on Sp5 to promote mESC self-renewal. Forced Sp5 expression can reproduce partial effects of Wnt/β-catenin signaling but mimics most features of LIF–Stat3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…SP5, which shares limited domain homology with the ubiquitous SP1 transcription factor (Supplementary Fig. 1h ), has previously been described as a WNT/β-catenin target gene 12 , 14 18 . Immunoblotting with an antibody directed against the amino-terminus of SP5 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SP5, which shares limited domain homology with the ubiquitous SP1 transcription factor (Supplementary Fig. 1h ), has previously been described as a WNT/β-catenin target gene 12 , 14 18 . Immunoblotting with an antibody directed against the amino-terminus of SP5 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overlapping PCR was used to generate the Gsk3α-L195G, Gsk3α-K148R (kinase-dead) , Gsk3β-L132G, Gsk3β-K85R (kinase-dead) mutations. ES cells were transfected with PiggyBac vector (Ye et al, 2016) carrying various GSK3 mutants using Lipofectamine LTX (Invitrogen) according to the manufacturer’s instructions. Selection began one day after transfection by adding puromycin/hygromycin/blasticidin/zeocin and continued for one week or until the untransfected cells were all killed by the antibiotics in the untransfected control group.…”
Section: Star*methodsmentioning
confidence: 99%
“…Our previous report showed that Sp5 is a downstream target of STAT3 and overexpression of Sp5 is sufficient to maintain the undifferentiated state of mESCs in the absence of LIF [ 15 ]. Sp5, a member of the Sp1 family, is characterized by the presence of three typical zinc finger domains belonging to the specificity protein/Krϋppel-like factor (Sp/Klf) superfamily [ 18 ].…”
Section: Introductionmentioning
confidence: 99%